Implementasi Pembelajaran Berbasis Proyek Berbantuan Aplikasi Simurelay untuk Meningkatkan Kreativitas Siswa - Rifqi, Ahmad; Haryudo, Subuh Isnur (Jurnal Pendidikan Madrasah, 2024)
This study was focused on identifying the increase in student creativity in project-based learning in classes that use the Simurelay application with classes that use powerpoint as a learning medium, and there are significant differences between the two classes. The research method used in this study is a quasi-experiment with a non-equivalent control group design of a design. This study involved the population of students in class XI TITL SMK YPM 1 Taman Sidoarjo. The research sample of 76 students was divided into 38 students in the control class and 38 in the control class who were selected with the purposive sampling technique. The data collection instrument was in the form of 30 multiple-choice questions. The data analysis techniques used are descriptive and inferential analysis. The results of data analysis showed that there was an increase in creativity before and after being treated in the experimental class with an average score of 19.79 with the category of moderately creative while in the control class obtained an average score of 15.18 with the category of non-creative. There was a significant difference in creativity between the two classes with (t-count = 6.8778 > t-table = 1.993) at a significance level of 5%. The application of the PjBL learning model assisted by Simurelay in the category is quite effective in increasing the creativity of students in class XI TITL SMK YPM 1 Taman Sidoarjo. In this study, students showed an excellent response after the learning model was applied.